The material life of Roman slaves - Joshel, Sandra Rae, 1947- (Cambridge, UK ; New York)
xv, [16] sayfa resim, plan, 286 sayfa
Keywords: “The Material Life of Roman Slaves is a major contribution to scholarly debates on the archaeology of Roman slavery. Rather than regard slaves as irretrievable in the ruins of ancient Roman cities and villas, the book takes the archaeological record as a key form of evidence for reconstructing slaves lives and experiences. Interweaving literature, law, and material evidence, the book searches for ways to see slaves in these various contexts-to make them visible where texts tell us they were in fact present” --